N6-methyladenosine-methylomic landscape of lung tissues of mice with chronic obstructive pulmonary disease - Hu, Tingting; Xu, Lijuan; Jiang, Min; Zhang, Fengbo; Li, Qifeng; Li, Zhiwei; Wu, Chao; Ding, Jianbing; Li, Fengsen; Wang, Jing (Frontiers in Immunology, 2023)
Abstract Chronic obstructive pulmonary disease (COPD), a common respiratory disease, can be divided into stable phase and acute exacerbation phase (AECOPD) and is characterized by inflammation and hyper-immunity. Methylation of N6-methyladenosine (m6A) is an epigenetic modification that regulates the expression and functions of genes by influencing post-transcriptional RNA modifications. Its influence on the immune regulation mechanism has attracted great attention. Herein, we present the m6Amethylomic landscape and observe how the methylation of m6A participates in the pathological process of COPD. The m6A modification of 430 genes increased and that of 3995 genes decreased in the lung tissues of mice with stable COPD. The lung tissues of mice with AECOPD exhibited 740 genes with hypermethylated m6A peak and 1373 genes with low m6A peak. These differentially methylated genes participated in signaling pathways related to immune functions. To further clarify the expression levels of differentially methylated genes, RNA immunoprecipitation sequencing (MeRIP-seq) and RNA-sequencing data were jointly analyzed. In the stable COPD group, 119 hypermethylated mRNAs (82 upregulated and 37 downregulated mRNAs) and 867 hypomethylated mRNAs (419 upregulated and 448 downregulated mRNAs) were differentially expressed. In the AECOPD group, 87 hypermethylated mRNAs (71 upregulated and 16 downregulated mRNAs) and 358 hypomethylated mRNAs (115 upregulated and 243 downregulated mRNAs) showed differential expression. Many mRNAs were related to immune function and inflammation. Together, this study provides important evidence on the role of RNA methylation of m6A in COPD.